Integration of unmanned aerial vehicles and LTE: a scenario-dependent analysis - Ozpolat, Mumin; Al-Rubaye, Saba; Williamson, Alex A.; Tsourdos, Antonios (IEEE, 2022)
Commercial applications of Unmanned Aerial Vehicles (UAVs) are expected to be one of the disruptive technologies that can shape many activities spans from goods delivery to surveillance. To maximize the effectiveness of such UAV applications, it is very important to enable beyond-line-of-sight (BLoS) communications. Hence, integrated UAV with LTE network can be used to extend UAV operations beyond visual line-of-sight (BVLOS) communications. This paper investigates the ability of Long-Term Evolution (LTE) network to provide coverage for UAV in such rural and urban area, in particular for the uplink video transmission. The system design takes into consideration the dependency of the large-scale path loss, shadowing and line-of-sight probability on the height of the UAV in the simulation environment, which is obtained from industrial measurements, and a real-world communication infrastructure layout and configuration. Results show that UAV height is a very critical factor in terms of delay and jitter performance for urban micro scenarios, and less effective in urban macro scenarios. Nevertheless, average throughput performance is less sensitive to the change in parameters and communication environments when the application type is set as a 1080p-quality video feed. Besides, mobility performance is explored for different system parameters such as hysteresis margin, time-to-trigger under various communications scenarios. Finally, the finding presented in this paper can be a roadmap to facilitate UAV-LTE integration in the near future.
Keywords: LTE; UAV; handover; BLOS